Analysing the impact of stakeholder relationships in the optimisation of biomass supply chains. (December 2022) - Ooi, Wu Jie; How, Bing Shen; KS Ng, Denny; Yin Ng, Lik; Andiappan, Viknesh
Highlights: The biomass supply chain offers a greener energy alternative to address the global warming issue. Relationships among operators are important to the feasibility of a biomass supply chain. Conflict analysis provides a mathematical framework to model relationships among individuals. Conflict analysis was utilised in supply chain optimisation to capture the effect of the relationship to the supply chain. Opimal supply chain using conflict analysis implied higher biomass consumption. Abstract: Many policies have been rolled out to help biomass supply chains reach their greatest contribution to combat climate issues. However, policies are often undermined by the failure to capture the impact of policy on interactions among players in the supply chain. When players in the supply chain have different perspectives toward a given policy, it impacts the way they interact with one another. This was not considered in the existing literature. A conflict analysis approach is applied to evaluate the impact of the supply chain player's relationship on supply chain decisions. Conflict analysis can be incorporated to mathematically model the behaviours of each supply chain player towards specific proposals or policies. To illustrate the effectiveness of the proposed conflict analysis-embedded model, a case study on a biofuel supply chain based in Malaysia is analysed. In this study, players' reactions in the supply chain toward the three proposed government policies (transport subsidy, workforce reduction and production variation) are systematically modelled and used as an input for the supply chain optimisation. A comparison study is shown to benchmark the results obtained with and without conflict analysis. Based on the optimised results, the conflict analysis model called for a higher amount of empty fruit bunch (i.e., 2.7 times higher between empty fruit brunch sources and first layer storage) than the model without conflict analysis. The total cost associated with the supply chain also increased by 77% after relationships among players were considered (USD 4.5 million to USD 8.0 million). The higher cost and material from the model suggested that conflict reduces the effectiveness of material transfer by reducing the chances of successful trade within the supply chain. By foreseeing and considering the inefficiency of a supply chain in a model, policymakers can, therefore, possible to make more sound decisions. The proposed approach with these findings is crucial in notifying the policymakers of the true potential of their policy toward the supply chain.